2019
DOI: 10.3847/2041-8213/ab290b
|View full text |Cite
|
Sign up to set email alerts
|

Can the Superposition of Evaporative Flows Explain Broad Fe xxi Profiles during Solar Flares?

Abstract: The observation of the high-temperature (10 MK) Fe XXI1354.1 Å line with the Interface Region Imaging Spectrograph has provided significant insights into the chromospheric evaporation process in flares. In particular, the line is often observed to be completely blueshifted, in contrast to previous observations at lower spatial and spectral resolution, and in agreement with predictions from theoretical models. Interestingly, the line is also observed to be mostly symmetric and significantly broader than expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 49 publications
5
44
0
Order By: Relevance
“…"Quiet Sun" synthesis models have started to consider the advantages of these accurate, self-consistent hydrogen broadening profiles as well (Bjørgen et al 2019;Marchenko et al 2021). Here we describe the implementation of new line profile functions in the state-of-the-art RHD code RADYN, which is widely used for simulations of a wide variety of solar flare phenomena (Simões et al 2017;Polito et al 2019;Sadykov et al 2020;Monson et al 2021), Ellerman bombs (Hong et al 2017;Reid et al 2017), nanoflares (Testa et al 2014;Polito et al 2018), and chromospheric dynamics such as spicules and shocks (Carlsson & Stein 2002;Wedemeyer-Böhm & Carlsson 2011;Guerreiro et al 2013;Molnar et al 2021). The updated hydrogen line profile functions are known as the TB09+HM88 profiles, which are extensions of the VCS unified theory calculations to higher-n j lines with self-consistent, non-ideal broadening from electron collisions and proton/ion perturbations.…”
Section: Discussionmentioning
confidence: 99%
“…"Quiet Sun" synthesis models have started to consider the advantages of these accurate, self-consistent hydrogen broadening profiles as well (Bjørgen et al 2019;Marchenko et al 2021). Here we describe the implementation of new line profile functions in the state-of-the-art RHD code RADYN, which is widely used for simulations of a wide variety of solar flare phenomena (Simões et al 2017;Polito et al 2019;Sadykov et al 2020;Monson et al 2021), Ellerman bombs (Hong et al 2017;Reid et al 2017), nanoflares (Testa et al 2014;Polito et al 2018), and chromospheric dynamics such as spicules and shocks (Carlsson & Stein 2002;Wedemeyer-Böhm & Carlsson 2011;Guerreiro et al 2013;Molnar et al 2021). The updated hydrogen line profile functions are known as the TB09+HM88 profiles, which are extensions of the VCS unified theory calculations to higher-n j lines with self-consistent, non-ideal broadening from electron collisions and proton/ion perturbations.…”
Section: Discussionmentioning
confidence: 99%
“…Doschek et al, 1986;Milligan, 2011). By using 1D hydrodynamic simulations of multi-thread flare loops mimicking a 3D geometry, Polito, Testa, and De Pontieu (2019) found that this scenario may not be compatible with the IRIS Fe XXI profiles, which appear to be broad but at the same time symmetric and well fitted with a single Gaussian profile (Figure 22), and they suggested that other mechanisms such as Alfvénic turbulence or non-equilibrium ionization might need to be invoked to explain the observations.…”
Section: Chromospheric Evaporation and Condensation With Irismentioning
confidence: 98%
“…For instance, hydrodynamic models including non-equilibrium ionization for highly charged iron atoms using the HYDRAD code (Bradshaw and Mason, 2003) appear to reproduce some of the observed features, such as the broad and symmetric profiles in hot lines, assuming short flare loops and a combination of input parameters (Mandage and Bradshaw, 2020). However, simulations of longer loops with lengths 50 Mm, such as the ones observed in the 10 September 2014 flare analyzed by Polito, Testa, and De Pontieu (2019), still show profiles with blue-wing asymmetries that are not seen in the observations. Further investigation into the parameter space of these models and inclusion of additional heating mechanisms, such Alfvén waves, might be needed to solve some of these discrepancies.…”
Section: Chromospheric Evaporation and Condensation With Irismentioning
confidence: 99%
See 1 more Smart Citation
“…Although Fe XXI has provided crucial model constraints for chromospheric evaporation, the physical mechanism responsible for the nonthermal >100 km s −1 widths at flare footpoints remains elusive. A recent study by Polito et al (2019) used hydrodynamic models to dismiss the most popular explanation of subresolution plasma flows at different velocities, showing that an additional physical mechanism, such as plasma turbulence or very large ion temperatures is necessary for a complete explanation. A speculative dismissal of the superposition scenario was already put forward several decades earlier by Antonucci et al (1986), who noted that it would be unlikely for up-and down-flowing material to exactly balance each other to produce the archetypal symmetric Fe XXI profile commonly observed.…”
Section: Spectral Linesmentioning
confidence: 99%